The history of malaria in Sã Tomé. Considerations on an epidemic. - Baptista, J L (Acta Médica Portuguesa, 1996)
Using a historical approach of malaria control in the island of São Tomé, the author describes the evolution of strategies used with special reference to the last 25 years. From a zero mortality rate in children under 4 years in 1981/83, malaria became the first cause of morbidity and mortality after the epidemic of 1985/86. Malaria was introduced in 1493, when the virgin island was populated with individuals of various origins (Europe, Africa). The problem became more important as the population of São Tomé increased in the XIXth century, with immigration of workers for cultivation of coffee and cocoa. At that time, methods of control of "fevers" were already defined including drainage of swamps, cleansing of the environment and use of quinine for prophylaxis and treatment. At the beginning of the XXth century, with the first epidemiological investigations, global plans of medical assistance and free delivery of chloroquine were elaborated. Between 1946 and 1967, localities were stratified according to their endemicity, the major vectorial species (Anopheles gambiae sp.) were identified and the parasitological indices were calculated. All species of the malarial parasites coexisted, Plasmodium falciparum being the most prominent. In 1968, the Mission of Eradication of Malaria was created. Between 1977 and 1983, anti-vectorial control (indoor spraying, larvicides) resulted in a decrease of mortality rate. The interruption of the antivectorial control activities was responsible for the 1985/86 epidemic and the restoration of the levels of endemicity.